2018
DOI: 10.4314/bajopas.v10i1.84s
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of protocol for multiple shoots regeneration from apical meristem of embryonic axes in cowpea (<i>Vigna unguiculata</i> L. Walp)

Abstract: In this work, we report a new approach for meristem of embryonic axes in four elite cowpea varieties. The hypocotyl and primordial leaves were removed and embryonic axes were placed in culture bottles containing Murashige and Skoog basal + B5 vitamins (MSB5) fortified with 22.2µM, 26.6µM or 31.0µM N 6-benzylaminopurine (BAP obtained on regeneration media consisting of MSB5 supplemented with low concentration (2.22µM) of BAP. Hormone free media promoted direct regeneration of single shoots from the apical meris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…De novo shoot organogenesis using EA as explants A rapid, efficient and reproducible regeneration system is a prerequisite for establishment of an efficient cowpea genetic transformation system. Although several studies of in vitro regeneration of cowpea based on organogenesis have been reported (Aasim et al, 2010;Abdu Sani et al, 2015;Mamadou et al, 2008;Manman et al, 2013;Odutayo et al, 2005;Raveendar et al, 2009;Sani et al, 2018;Tie et al, 2013;Yusuf et al, 2008), an efficient cowpea regeneration system that enables highly efficient transformation is still lacking (Manman et al, 2013). Soybean (Glycine max) transformation based on the pre-existing meristems of EA explants has been well established and provides a reliable and highly efficient means for introducing transgenes (Aragão et al, 2000;Liu et al, 2004;Turlapati et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…De novo shoot organogenesis using EA as explants A rapid, efficient and reproducible regeneration system is a prerequisite for establishment of an efficient cowpea genetic transformation system. Although several studies of in vitro regeneration of cowpea based on organogenesis have been reported (Aasim et al, 2010;Abdu Sani et al, 2015;Mamadou et al, 2008;Manman et al, 2013;Odutayo et al, 2005;Raveendar et al, 2009;Sani et al, 2018;Tie et al, 2013;Yusuf et al, 2008), an efficient cowpea regeneration system that enables highly efficient transformation is still lacking (Manman et al, 2013). Soybean (Glycine max) transformation based on the pre-existing meristems of EA explants has been well established and provides a reliable and highly efficient means for introducing transgenes (Aragão et al, 2000;Liu et al, 2004;Turlapati et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…De novo shoot organogenesis using EA as explants A rapid, efficient and reproducible regeneration system is a prerequisite for establishment of an efficient cowpea genetic transformation system. Although several studies of in vitro regeneration of cowpea based on organogenesis have been reported (Aasim et al, 2010;Abdu Sani et al, 2015;Mamadou et al, 2008;Manman et al, 2013;Odutayo et al, 2005;Raveendar et al, 2009;Sani et al, 2018;Tie et al, 2013;Yusuf et al, 2008), an efficient cowpea regeneration system that enables highly efficient transformation is still lacking (Manman et al, 2013). Soybean transformation based on the preexisting meristems of EA explants has been well established and provides a reliable and highly efficient mean for introducing transgenes (Aragão et al, 2000;Liu et al, 2004;Turlapati et al, 2008).…”
Section: Resultsmentioning
confidence: 99%